Review of Bob Downes Open Music: Episodes at 4 A.M., A Touch of the Sun: Milk Teeth, Chamberpot, Jan Steele: John Cage: Voices and Instruments, and Michael Nyman: Decay Music - Roberts, David (Contact: A Journal for Contemporary Music (1971-1990), 1977)